Demonstration Project: Transitioning a Research Network to New Single IRB Platforms. Issue 6 (31st October 2022) - Burr, Jeri S.; Johnson, Ann; Risenmay, Annie; Bisping, Stephanie; Serdoz, Emily S.; Coleman, Whit; Sward, Katherine A.; Rothwell, Erin; Dean, J. Michael
ABSTRACT: Since the 2016 National Institutes of Health (NIH) mandate to use a single IRB (sIRB) in multicenter research, institutions have struggled to operationalize the process. In this demonstration project, the University of Utah Trial Innovation Center assisted the Collaborative Pediatric Critical Care Research Network to transition from using individually negotiated reliance agreements and paper‐based documentation to a new sIRB master agreement and an informatics platform to capture reliance documentation. Lessons learned that can guide other academic institutions and IRBs as they operationalize sIRBs included the need for sites to understand what type of engagement or reliance is required and their need to understand the difference between reliance and activation. Requirements around local review remain poorly understood. Further research is needed to determine approaches that can achieve the NIH vision of reviews becoming more efficient and improving study start‐up times, relieving administrative burden while advancing human research protections.